PERBANDINGAN ZAKAT DAN PAJAK (IMPLEMENTASI RELIGIUSITAS ZAKAT DALAM PERPAJAKAN SEBAGAI UPAYA MENCEGAH TAX AVOIDANCE) - Anne Putri; Aries Tanno (Tirtayasa Ekonomika, 2016)
Tax tax avoidance is a major problem faced by many countries. The government imposed sanctions clear to its citizens to ensure the implementation of tax payments. Unlike taxes which have clear and firm sanctions, lack of supervision and sanction the payment of zakat does not preclude the public to carry out their zakat obligation.Zakat and tax is a compulsory payment without any contra directly to the payer. The payment of zakat and taxes can be used to improve the welfare of the community. In general zakat equal to the zakat tax. Some experts said that charity is "islamic taxation" (Hafez, 2011).This study aimed to compare the concepts and principles between zakat and taxes. This study addresses the issue religiutas in the concept of Islam that exists in zakat and associates it with tax issues. Comparisons are made of the various aspects: legal, economic, social, ethical and spiritual. The implications are expected is that the principles can be applied zakat taxation so that it can be used as an alternative in reducing or preventing the tax avoidance problem that occurred.